OVARIAN CHANGES AND REPRODUCTIVE ORGAN STRUCTURE IN HYPOTHYROIDISM - Ziyoeva Gulrukh Pulot qizi (Modern American Journals, 2025)
Hypothyroidism, a condition characterized by reduced thyroid hormone secretion, profoundly influences multiple physiological systems, particularly the female reproductive system. The thyroid gland plays a vital role in maintaining homeostasis of reproductive hormones through its interaction with the hypothalamic-pituitary-gonadal axis. Alterations in thyroid function can disrupt ovulation, menstrual cycles, and fertility, leading to significant morphological and functional changes in the ovaries and other reproductive organs. This article aims to provide an in-depth analysis of ovarian and reproductive organ alterations observed in hypothyroidism, with a focus on histopathological, endocrine, and molecular perspectives. Through an examination of recent findings, this study highlights how thyroid hormone deficiency contributes to ovarian dysfunction, including follicular atresia, luteal insufficiency, and stromal fibrosis.
Keywords: Hypothyroidism, ovarian dysfunction, reproductive system, thyroid hormones, fertility, histopathology.